Tissue response to polyanionic collagen: elastin matrices implanted in rat calvaria - Rosa, F. P.; Lia, Raphael Carlos Comelli [UNESP]; de Souza, KOF; Goissis, G.; Marcantonio, E. (Elsevier B.V., 2003)
The tissue response to polyanionic collagen matrices, prepared from bovine pericardium and implanted subperiosteally in rat calvaria, was studied. The materials were implanted in 72 male rats (Rattus norvegicus, albinus, Holtzman), randomly divided into four groups: GI-MBP hydrolyzed for 24 h; GII-MBP hydrolyzed for 36 h; GIII-MBP hydrolyzed for 48 h; GIV-native M BP. The materials were explanted after 15, 30 and 60 days and analyzed by routine histological procedures. Except for group IV (native bovine pericardium), polyanionic collagen from groups GI, GII and GIII showed low inflammatory reaction associated with bone formation, partially or completely integrated to the cranial bone; group GIV was characterized by an intense inflammatory reaction with occasional dystrophic mineralization and with occasional bone formation at 60 days when there was a decrease in the inflammatory reaction. Thus, the MBP from groups I, II and III were biologically compatible, enhancing bone formation with a slight delay at 60 days in GII. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: Polyanionic collagen; Biocompatibility; Osteogenesis; Bone substitute